Lupus anticoagulant-hypoprothrombinemia syndrome with lupus nephritis in a girl misdiagnosed with immunoglobulin A nephropathy: a case report - Chung Ho Lee; Yo Han Ahn; Hee Gyung Kang; Ji Hyun Kim (Korean Society of Pediatric Nephrology, 2024)
Distinguishing lupus nephritis (LN) from other glomerulopathies, such as immunoglobulin A nephropathy (IgAN), poses a diagnostic challenge owing to overlapping clinical and histopathologic findings. Lupus anticoagulant-hypoprothrombinemia syndrome (LAHPS) is a rare and potentially fatal disorder characterized by the presence of lupus anticoagulant and acquired factor II deficiency. We report a pediatric case of LN with LAHPS, which was initially diagnosed as IgAN. An 8-year-old girl presented with gross hematuria with nephrotic syndrome. Based on the kidney biopsy results, treatment for IgAN with membranoproliferative pattern was initiated. Two months later, she developed left upper extremity swelling with multiple vein thromboses requiring anticoagulation; treatment led to remission, allowing discontinuation of immunosuppressants within 8 months. Gross hematuria recurred 10 months later and was accompanied by hypocomplementemia; positive antinuclear, anti-double stranded DNA, and triple antiphospholipid antibodies; and factor II deficiency, prompting revision of the diagnosis to LN and LAHPS. Initial delay in LN diagnosis was attributed to the patient's young age, nonspecific symptoms, and inconclusive laboratory and histopathological findings. Immunosuppressive therapy for IgAN partially improved LN, further complicating the diagnosis. This case emphasized the importance of clinical suspicion; integrating clinical, serological, and histopathological data; and considering LAHPS in differential diagnosis of glomerulonephritis with coagulopathy.